On Some Summation Identities - Corcino, Robert; Corcino, Christina (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
In this paper we discuss two of these interesting techniques: interchanging the index of the summations and changing "product of sums" to "sum of products". Moreover, we establish a generalization of some well-known summation formulas which consequently give interesting and useful identities.